STUDY ON PROS AND CONS ARMY-POLICE ACTIVELY APPOINTED AS REGIONAL HEAD - Elsa Septia; Suswanta Suswanta; Muhammad Rizki Ramadhan; Maisarah Mitra Adrian (JWP (Jurnal Wacana Politik), 2023)
This study will identify the pros and cons of active ARMY/POLICE being appointed as regional heads in 2022. In its journey, Indonesia has changed in organizing general elections; from the beginning, the public was allowed to vote for candidates from 2004 to the present. Ahead of the Simultaneous Regional Head Elections in 2024, several regions in the country will experience a leadership vacancy due to the expiration of the terms of office of governors, and regents/mayors starting in 2022. To fill the vacancy in leadership positions, the government can appoint an official until simultaneous regional elections are held in November 2024. This becomes a problem because the appointment of active TNI-Polri officers as acting (Pj) regional heads has caused a polemic. This study uses qualitative research using secondary data from news and journals related to the research. The results of the study indicate that some support this, it can be done with a note that the active TNI/Polri in office must still be supervised, and the positions occupied are equivalent to their duties. However, not a few refuse because this can reduce the value of democracy, and the TNI/Polri, which should focus on state security, will bring back the Dual function (dwifungsi) of the Armed Forces, which can disrupt the political system in Indonesia.